Conceptual Model of Differentiated Learning Management in Elementary School - Rina, Rina; Hasanah, Enung (Tadbir : Jurnal Studi Manajemen Pendidikan, 2024)
This study examines the implementation of differentiated learning management at Al-Ilham Banjar Inspirational Elementary School, a dynamic instructional approach tailored to address the diverse needs of individual students. Differentiated learning aims to optimize each student's learning experience and outcomes by adapting teaching methods, yet it presents significant challenges for educators in terms of planning, resource allocation, and evaluation. Using a qualitative research methodology, including interviews, observations, and documentation, this study investigates the school's strategies in managing these challenges. The findings reveal a comprehensive, three-tiered approach: (1) assessing and identifying students' learning readiness and needs, (2) organizing and mobilizing resources, such as actively involving parents and employing specially designed teaching modules that align with differentiated instruction, and (3) implementing varied instructional strategies, allowing differentiation across content, learning processes, and final products to cater to diverse learning profiles. Additionally, the school employs formative and summative assessment methods to monitor and evaluate students’ progress continuously, ensuring that differentiated learning outcomes are achieved effectively. This management strategy demonstrates a strong potential to maximize each student's abilities, providing a structured framework that could serve as a valuable reference for other educational institutions looking to enhance their differentiated learning practices. This study thus contributes valuable insights for schools and educators interested in implementing effective differentiated learning management.